Kawasaki Disease like Multisystem Inflammatory Syndrome in a Toddler during SARS-CoV-2 Pandemic in Nepal - Rayamajhi, Ajit; Sharma, Manisha; Deo, Mukund Kumar; Shrestha, Sanjeet; Bista, Krishna Prasad; Paudel, Krishna Prasad (Journal of Nepal Health Research Council, 2021)
Multisystem inflammatory syndrome in children is a new childhood inflammatory disorder associated with respiratory syndrome coronavirus 2 (SARS-CoV-2). This illness of elevated inflammatory markers and multiple organ involvement similar to Kawasaki disease is not commonly reported from Asia. A 17-month-old boy presented with acute onset fever, rash, non-exudative conjunctivitis and swellings of hands and legs. In x-ray chest there was infiltration on the right lower lobe and echocardiography showed evidence of coronary arteritis. The diagnosis of multisystem inflammatory syndrome in children was confirmed on the basis of characteristic clinical features and laboratory parameters fulfilling standard case definition for multisystem inflammatory syndrome in children. The child responded to treatment with intravenous immunoglobulin and high dose aspirin. Hence, amidst SARS-CoV-2 pandemic, multisystem inflammatory syndrome in children should be suspected and effectively treated even in a country like Nepal. Keywords: Kawasaki disease; multiple inflammatory syndrome in children; Nepal; respiratory syndrome coronavirus 2